Corporate governance structures and firm performance in large agriculture companies in New Zealand. Issue 5 (1st October 2018) - Roudaki, Jamal
Abstract : Purpose: This study aims to explore the role of corporate governance (CG) characteristics on the financial performance of large agricultural companies in New Zealand. External auditor remuneration and board characteristics, such as board ownership, board compensation, board independence and board gender diversity, are addressed in the context of New Zealand's agricultural companies by applying agency theory. Design/methodology/approach: This paper uses a balanced panel data generalised least square regression analysis on 80 firm-years of observations over the period from 2012 to 2015. Findings: Empirical analysis revealed that external auditors' remuneration and board characteristics, such as board compensation and board independence, except for board ownership and board gender diversity, held no association with the agricultural companies' performance. While board ownership and board gender diversity were negatively, but significantly, associated with firm performance, these results were pronounced in the listed agricultural companies rather than in the non-listed companies. Research limitations/implications: This study encountered limitations commonly associated with the majority of industry-specific studies, i.e. small sample size and lack of published financial information from databases. Therefore, for generalisation, these limitations were considered relevant. Practical implications: The results of this research project are beneficial for authorities and agricultural company directors in implementing CG principles and guidelines to empower such companies in international competition. Encouraging agricultural companies to maintain a high level of transparency in financial reporting is of central interest for the government's economic development, and stock market investors achieve a high level of transparency in non-financial disclosures, the chief objective of this study. Finally, the results of this paper may encourage auditors to scrutinise CG disclosures by agricultural companies in more detail, looking for undisclosed information. Social implications: The results of this paper may encourage managerial transparency by providing appropriate disclosures for the public benefit. Investors may benefit from the disclosure provided in their economic decision-making and the public may expand on the information disclosed in facilitating development through exports, expansion of foreign investments and the indigenous economy. Originality/value: The findings contribute to the literature by providing novel and original insights into using a sample of listed and non-listed agricultural companies to extend the current understanding of the governance-performance nexus.